Transient, Marked ST-Segment Elevation During Successful Epicardial Substrate Ablation in a Patient With Brugada Syndrome - Fujino, Tadashi (JACC Case Rep, 2019)
A 37-year-old man with Brugada syndrome and frequent appropriate implantable cardioverter-defibrillator shocks received an epicardial substrate ablation. During the procedure to eliminate delayed potentials, transient, marked ST-segment elevation in lead V(2) was observed, particularly in the anterior right ventricle with a borderline between normal and low-voltage areas. (Level of Difficulty: Intermediate.)